(untitled) (Journal of Comparative & International Higher Education, 2022)
Globally, nations are still dealing with numerous challenges in higher education that include access, participation, equity and relevance. Despite efforts made to improve access, Malawi still struggles to provide higher education to its growing youth population. Up to 60% of eligible university candidates may not be accepted due to limited infrastructure and facilities, while less than 1% of Malawi’s qualified cohort get enrolled in some form of tertiary education. As a result, this study explores alternative higher education programmes offered in Malawi. Efforts are being made to enhance youth access to higher education, and yet there is limited knowledge on whether these alternative higher educational programmes meet the youth’s aspirations. The study uses a qualitative case study based on the views of youth from a selected NGO. The study examines the youth’s unique experiences of alternative education programmes to determine how these initiatives prepare them to live meaningful lives that they have a reason to value, aspire towards and enhance their wellbeing. The study addresses the need for studies in higher education in Malawi and employs the capabilities approach framework in a country that concentrates on basic education. It envisages contributing to policy formulation, practice and evaluation to meet youth aspirations and aid their capability formation and enhancement. The study also aims to contribute to refining the capabilities approach scholarship within the higher education landscape.